2009
DOI: 10.1089/dia.2007.0299
|View full text |Cite
|
Sign up to set email alerts
|

Regular Visits to a Diabetes Clinic Were Associated with Lower Magnitude of Visual Disability and Diabetic Retinopathy—A Hospital-Based Historical Cohort Study in Yemen

Abstract: The presence of DR and visual disabilities among patients with diabetes is associated with irregular attendance at diabetes clinics. The regularity of medical visits seems to be a proxy indicator of better primary prevention of eye complications of DM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 15 publications
0
21
0
Order By: Relevance
“…Additionally, even with perfect implementation in clinics, this method of ‘static’ outreach may not reach people who do not go to clinics for their treatment . A study in Yemen suggested that this population is at even greater risk for severe DR …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, even with perfect implementation in clinics, this method of ‘static’ outreach may not reach people who do not go to clinics for their treatment . A study in Yemen suggested that this population is at even greater risk for severe DR …”
Section: Resultsmentioning
confidence: 99%
“…15 Additionally, even with perfect implementation in clinics, this method of 'static' outreach may not reach people who do not go to clinics for their treatment. 65 A study in Yemen suggested that this population is at even greater risk for severe DR. 70 The approach of 'static' outreach through existing diabetes clinics has been tested in some areas. In particular, a study by Liu et al in China trained GPs to take photographs, which were read by a reading centre.…”
Section: Screening Infrastructurementioning
confidence: 99%
“…Females had a statistically significantly higher rate of DR in our study. Although gender was not found to be an important risk factor for developing DR in most other studies [17,[24][25][26][27][28] , some found males to be more prone to develop DR than females, as in UAE [21] and Oman [23] .…”
Section: Risk Factors For Drmentioning
confidence: 90%
“…[27] A study in Yemen showed that presence of DR and visual disability among patients with diabetes is associated with irregular attendance of diabetes clinic. [28] PDR was associated with tangential traction band in few patients [ Figure 3]. Other features of DR such as neovascular glaucoma (NVG) and retinal detachment were not observed in the patients studied.…”
Section: Discussionmentioning
confidence: 99%